Kampung Hijau Produktif Sebagai Penerapan Corporate Social Responsibility - Ompang Reski Hasibuan; Eko Setyawan; Dewi Luqmania; Eka Setia Budi; Baling Kustriyono; Suyatno Suyatno; Totok R. Biyanto (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2019)
This research background is the establishment of a legal rule regarding Corporate Social Responsibility (CSR) in 2007. This study aims to discuss the positive impact of CSR implementation by companies in Kramatinggil, Gresik, East Java. The research subjects are the people who are the majority have a high school education background. The method used in the study of the application of CSR is a qualitative descriptive method. The qualitative approach in this research uses a phenomenological. Data processing, in this case, is done by categorising field notes from the results of depth interviews. Data processing is also done from the effects of survey data that has been processed and then narrated and from the impact of FGD (Focus Group Discussion) conducted for beneficiaries. The result shows that the community have proven to be successful in increasing the ratio of gardens to the entire space used by the application of vertical gardens and Planting Fruits in Pot (Tabulampot). The activity showed that the company's CSR in the Kramatinggil area had succeeded in conserving natural resources and the welfare of the surrounding population.